Ultrastructure of the ovary of Dermatobia hominis (Diptera: cuterebridae). I. Development during the 3rd larval instar - Gregorio, E. A. [UNESP]; Secco, V. N. D. P. [UNESP]; Toledo, L. A. [UNESP]; Lello, E. [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1990)
The ultrastructure and distribution of gonial and somatic cells in the ovary of Dermatobia hominis was studied during the 3rd larval instar. In larvae weighing between 400 and 500 mg, the ovary is partially divided into basal and apical regions by oblong somatic cells that penetrate from the periphery; these cells show ovoid nucleus and cytoplasm full of microtubules. In both regions, gonial cells with regular outlines, large nucleus and low electron-density cytoplasm are scattered among the interstitial somatic cells. These later cells have small nucleus and electrodense cytoplasm. Clear somatic cells with small nucleus and cytoplasm of very low electron-density are restrict to the apical region of the gonad. Degenerating interstitial somatic cells are seen in the basal portion close to the ovary peduncle. During all this larval period the morphological features of the ovary remain almost the same. At the end of the period there is a gradual deposition of glycogen in the cytoplasm of the somatic cells, increase in the number and density of their mitochondria plus nuclear modification as membrane wrinkling and chromatin condensation in masses.
Keywords: ovary; bot-fly; Diptera; Dermatobia hominis